Customers Perspective with Respect to Payment Apps in Rural Area: A study of selected village of Sonipat - Kumar, Ramesh (East Asian Journal of Multidisciplinary Research, 2024)
This comprehensive study, conducted in a selected village of Sonipat, examines the customers' perspective towards payment apps in a rural setting, in line with India's "Digital India" initiative. The study encompasses an extensive demographic analysis and hypothesis testing, revealing key insights into the adoption, usage, and perception of digital payment applications among rural populations. The research, which involves a sample size of 120 individuals, primarily focuses on understanding customer satisfaction, trends, challenges, and the impact of these payment apps. Key findings indicate a predominant use among younger, educated males, with Google Pay being the most favored app. Despite the growing trend towards digitalization, traditional payment methods still persist, highlighting a gradual transition in financial behavior. The study also points out the critical role of gender in technology adoption and notes the necessity for inclusive digital literacy programs. Overall, the study contributes valuable insights into the evolving landscape of digital payments in rural India, highlighting both progress and areas needing attention for a more comprehensive digital integration.